Application of Cymbopogon nardus as a control of Plant Disturbing Organism Cercospora leaf spot in chili (Capsicum anuum L.) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2025)
Chili (Capsicum annuum L.) is one of the most valuable agricultural commodities in Indonesia and is always in demand. One of the most common problems encountered in the cultivation of this crop is the presence of diseases that affect the plant, one of which is Cercospora leaf spot. Using environmentally friendly materials to control plant diseases is currently a necessary factor. The application of Cymbopogon nardus as a plant disease controller has been widely adopted. The author was interested in testing the ability of C. nardus to control Cercospora leaf spot disease in chilli plants. The study was conducted in the ATC (Agriculture Training Centre) field trial in South Sumatra. Pathogen identification was carried out in the Phytopathology Laboratory, Department of Pest and Disease Management, Faculty of Agriculture, Sriwijaya University. The results of the study showed that the application of a C. nardus concentration of 6.25 mL/5 L resulted in the lowest leaf spot growth at observations 12 and 13. Using C. nardus extract for control is an environmentally friendly method that can be used for control.